1996
DOI: 10.1159/000213764
|View full text |Cite
|
Sign up to set email alerts
|

Training Influence on Age-Dependent Changes in the Gait of Rats

Abstract: Stride length, stance width and gait symmetry were measured as parameters of gait analysis in young (5 months) and old (28 months) Sprague-Dawley rats following 3 months of treadmill running as well as in sedentary controls. Stride length decreased significantly with age and increased significantly following training in both young and old rats. Means of stance width increased significantly with age, but were unaffected by training. Gait symmetry declined with age; however, treadmill running counteracted the de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2005
2005
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 33 publications
0
6
1
Order By: Relevance
“…However, it includes the metrics Gait Symmetry which computes the ratio of forelimb stepping frequency to hind limb stepping frequency. It has been shown that the parameter Gait Symmetry declines with age and treadmill training counteracted the decline of Gait Symmetry [56]. Of note, no differences with respect to the parameter Gait Symmetry were found during the pre-clinical EAE phase in our current study.…”
Section: Discussioncontrasting
confidence: 48%
“…However, it includes the metrics Gait Symmetry which computes the ratio of forelimb stepping frequency to hind limb stepping frequency. It has been shown that the parameter Gait Symmetry declines with age and treadmill training counteracted the decline of Gait Symmetry [56]. Of note, no differences with respect to the parameter Gait Symmetry were found during the pre-clinical EAE phase in our current study.…”
Section: Discussioncontrasting
confidence: 48%
“…Another explanation may be that the motor‐planning strategy used for voluntary exercise changes with age and results in less mechanical strain in the QUAD muscle compared with other muscles. Stride length also diminishes with age in humans45 and rats46 and this would also reduce the stress placed on QUAD muscle with age. Decreased SC activation may be one reason why aged muscle does not hypertrophy to the same extent as young muscle when exposed to physical activity.…”
Section: Discussionmentioning
confidence: 99%
“…Clearly, methods involving reviews of videotape frames without the use of ink imprinting, as we have done here are more ideal. Another technique commonly used is the treadmill method in which gait is assessed while the animal runs on a motorized treadmill (Dorner et al, 1996;Nessler et al, 2006). This technique provides an accurate assessment of several gait parameters at adjustable speeds and inclinations.…”
Section: Discussionmentioning
confidence: 99%